Accumulation by Dispossession in Tourism - Schmid, Karl (Anthropologica, 2015)
Accumulation by dispossession (ABD) is deeply implicated in the broad history of tourism development at Luxor, Egypt. ABD informs a theme of loss found in ethnographic, historical and archival sources in three significant periods of tourism development: the formative period of tourism extend ing to the mid-18th century, the following mass tourism era and the post-1970s period. Dispossessions including the absence of consent, violent appropriations, monopolistic practices, repeated displacements and the policing of space belie the discourse of tourism as exchange or economic development and reveal differently scaled dimensions of the exercise of power and hierarchy.